Emr1 regulates the number of foci of the endoplasmic reticulum-mitochondria encounter structure complex - Faiz Rasul (Nature Portfolio, 2021)
Interorganelle membrane contact sites between the endoplasmic reticulum and mitochondria can be mediated with the ER-mitochondria encounter structure (ERMES) complex, though precise regulation is unclear. Here, the authors report that the number of ERMES foci is regulated by the previously uncharacterized mitochondrial membrane protein Emr1.